2024
DOI: 10.1186/s13104-024-06745-4
|View full text |Cite
|
Sign up to set email alerts
|

Time-course of balance training-related changes on static and dynamic balance performance in healthy children

Thomas Muehlbauer,
Michael Giesen,
Nele Roß
et al.

Abstract: Objective In healthy children, there is evidence of improvements in static and dynamic balance performance following balance training. However, the time-course of balance training-related changes is unknown. Thus, we determined the effects of balance training after one, three, and six weeks of exercise on measures of static and dynamic balance in healthy children (N = 44, 20 females, mean age: 9.6 ± 0.5 years, age range: 9–11 years). Results Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Previous research [ 17 ] has reported medium- to large-sized effect sizes that were used for sample size estimation. Precisely, a G*power analysis (effect size f = 0.25, α error probability = 0.05, 1-β error probability = 0.80, correlations among repeated measures r = 0.40, 2 groups, 2 assessments, drop-out rate of 10% due to reasons not attributable to treatment) revealed that a total sample size of N = 40 participants (i.e., n = 20 per group) would be sufficient to detect significant treatment effects [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous research [ 17 ] has reported medium- to large-sized effect sizes that were used for sample size estimation. Precisely, a G*power analysis (effect size f = 0.25, α error probability = 0.05, 1-β error probability = 0.80, correlations among repeated measures r = 0.40, 2 groups, 2 assessments, drop-out rate of 10% due to reasons not attributable to treatment) revealed that a total sample size of N = 40 participants (i.e., n = 20 per group) would be sufficient to detect significant treatment effects [ 18 ].…”
Section: Methodsmentioning
confidence: 99%